Akibat Hukum dari Penyalahgunaan Wewenang oleh Panti Asuhan terhadap Anak Asuh dalam Penggunaan Live Sosial Media (Tiktok) menurut Perspektif Hukum Perlindungan Anak - Nissya Maulydha Hikmah; Husni Syawali (UNISBA Press, 2024)
Abstract. Orphanage is a place where human beings are humanized, as this orphanage is a place for nurturing and educating children as an alternative last resort to replace the role of a family that has lost its function. In the current era of technology development, donations or assistance for orphanages given by the public are now done through the use of social media with different platforms such as billboards, Instagram, and TikTok. However, there are still some orphanages that exist without being known because they are not registered with the local Social Services Agency. Due to this, there have been cases of abuse of authority by orphanage managers who solicit contributions or donations using the TikTok platform for personal gain, resulting in the rights of the foster children within the orphanage not being fulfilled.Based on the above description, the writer formulates several issues as follows: First, what is the legal protection for foster children as a result of the misuse of live social media (TikTok) by the managers? Second, how is the implementation of the responsibility of orphanage managers towards foster children from the perspective of child protection law? The purpose of this research is to determine the legal protection provided for foster children and the implementation of the responsibility of orphanage managers according to the perspective of child protection law. The research method used is normative juridical, which primarily relies on secondary data supported by primary data as additional sources. This research is descriptive-analytical in nature and is related to legal theory and the implementation of positive law, aiming to obtain answers to the research problems.The results obtained indicate that the protection provided for foster children is the action taken by the Social Services Agency, which provides temporary care based on the Child Social Welfare Institution by LKSA, facilitates and supports alternative family-based care in accordance with the National Standards for Child Care. Furthermore, the implementation of accountability for orphanage managers includes a prison sentence of 5 years and additional penalties such as the return of money, goods, or assets that have been diverted or distributed from the Foundation.